2018
DOI: 10.1002/anie.201810065
|View full text |Cite
|
Sign up to set email alerts
|

A Near‐Infrared Photoswitchable Protein–Fluorophore Tag for No‐Wash Live Cell Imaging

Abstract: FR-1V, a fluorene-based aldehydic chromophore, binds its target protein as an imine to yield a highly bathochromic pigment, CF-2, a prototypic protein-dye tagging system whose NIR emission can be spatiotemporally switched ON by rapid UV-light activation. This is achieved through photoisomerization of the imine and its subsequent protonation. We demonstrate a nowash protocol for live cell imaging of subcellular compartments in a variety of mammalian cell lines with minimal fluorescence background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…As targeting moieties, antibodies are limited due to their large size, complicated production methods and high cost. Small peptides offers an alternative strategy with lower immunogenicity and price of use as therapeutic agents or targeting groups for effective targeted cancer therapy . Targeting moieties, Arg‐Gly‐Asp (RGD) and Asn‐Gly‐Arg (NGR) have been used to interact with integrin avb3 (CD51/CD61) and aminopeptidyl N (CD13) receptors, which are highly expressed in angiogenic tumors or other tissues with angiogenic components .…”
Section: Peptide‐conjugated Nanomaterialsmentioning
confidence: 99%
“…As targeting moieties, antibodies are limited due to their large size, complicated production methods and high cost. Small peptides offers an alternative strategy with lower immunogenicity and price of use as therapeutic agents or targeting groups for effective targeted cancer therapy . Targeting moieties, Arg‐Gly‐Asp (RGD) and Asn‐Gly‐Arg (NGR) have been used to interact with integrin avb3 (CD51/CD61) and aminopeptidyl N (CD13) receptors, which are highly expressed in angiogenic tumors or other tissues with angiogenic components .…”
Section: Peptide‐conjugated Nanomaterialsmentioning
confidence: 99%
“…Human cellular retinol binding protein II (hCRBPII) chaperones both retinol and retinal within the cell. Our group has engineered these templates to create rhodopsin mimics used to understand protein‐based absorption tuning, protein‐directed photoisomerization pathways, [35–37] new classes of fluorescent and photoswitchable fluorescent protein tags, [38] and pH sensors [39,40] . We recently reported that some variants of hCRBPII give rise to domain‐swapped (DS) dimers [41] .…”
Section: Figurementioning
confidence: 99%
“…Our group has engineered these templates to create rhodopsin mimics used to understand protein-based absorption tuning, protein-directed photoisomerization pathways, [35][36][37] new classes of fluorescent and photoswitchable fluorescent protein tags, [38] and pH sensors. [39,40] We recently reported that some variants of hCRBPII give rise to domain-swapped (DS) dimers. [41] We then exploited the hCRBPII DS dimer as a design template to engineer a new class of protein conformational switches, activated by ligand binding or environmental reduction potential, characteristics lacking in the monomeric fold of the protein.…”
mentioning
confidence: 99%
“…21,22 The donating uorene fragment allows for a high absorption cross section and accommodates efficient through-bond energy transfer to the acceptor fragment, which results in bright chromophores that emit at long wavelengths. [23][24][25] The central p-conjugated backbone is typically anked by a combination of hydrophobic and hydrophilic sidechains. The design of the central core largely dictates the uorescence emission prole, 26,27 while the nature of these sidechains inuences the self-assembly behavior in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%